PSVII-20 Meta-analysis: Effect of increasing dietary calcium and phytase dose on phosphorus digestibility in weaning piglets and growing pigs. (5th December 2019) - Velayudhan, Deepak E; Marchal, Leon; Dersjant-Li, Yueming
Abstract: A meta-analysis was conducted to investigate the effect of dietary calcium (Ca) levels and phytase dose on apparent total tract digestibility (ATTD) of phosphorus (P) in pigs fed corn or wheat-based diets. A database was constructed using 19 studies (published and unpublished), contributing 766 data points with 464 in nursery pigs and 303 in growing pigs. A Buttiauxella sp. phytase was added at 4 doses (250, 500, 1, 000 and 2, 000 FTU/kg) to P and Ca deficient negative control diets (NC) among different studies. Total analysed dietary Ca, total P and calculated phytate P levels varied from 0.41 to 0.97%, 0.36 to 0.67%, and 0.21 to 0.31%, respectively among studies. Data were analysed using Mixed Model by JMP 14.0. Since no significant differences were observed in ATTD P between nursery pigs (average initial body weight 7.5kg) and growing pigs (average initial body weight 40.0kg), the data were combined for the meta-analysis. Nonlinear modelling was used to evaluate the effect of dietary Ca on ATTD P and P digestibility improvement over the NC at different phytase levels. Increasing phytase dose from 0 to 2000 FTU/kg, improved (P < 0.05) ATTD Ca and P in an exponential manner, with a greater ATTD P (P < 0.05) over NC. With multivariate analysis, ATTD P had a negative correlation (P < 0.05) with dietary Ca levels (-0.26), Ca:P ratio (-0.30) and dietary phytate content (-0.40). An interaction was found between Ca level and phytase dose for P digestibility improvement over NC, which was not significantly different at dose between 250 to 1000 FTU but increased (P < 0.05) at phytase dose of 2000 FTU/kg with increasing dietary Ca. These findings suggest that supplementation of 2000 FTU phytase /kg could restore Ca and P balance and mitigate the negative effects of increasing dietary Ca on P digestibility.